Evaluation of collaborative learning settings in 3D virtual worlds - Chang, Vanessa; Guetl, Christian; Kopeinik, S.; Williams, Robert (Kassel University Press GmbH, 2009)
Virtual 3D worlds are gaining popularity among the general population and the virtual world environment is widely used particularly by the younger generations as a knowledge and social tool. In recent years, universities have conducted experiments with the use of virtual 3D worlds for teaching and learning. Virtual 3D worlds are no longer just for the stereotypical geek. By 2011 it is estimated that about 80% of active Internet users will have an 'avatar' and /or a 'second life' in some form of virtual world environment. This paper attempts to contextualize the evolution and genererations of learners for learning in the 21st century. This paper presents a virtual learning environment created using Second Life equipped with four types of virtual space - collaborative area, common area, teacher-student meeting area, and social recreation area. An experiement is conducted involving university students who are enrolled in a unit with the aim of evaluating the use of Second Life for collaborative learning. A pre-survey evaluation was gathered followed by a post-survey evaluation. The positive results of these evaluations as well as lessons learned during the implementation phase are discussed in this paper.